1996
DOI: 10.1164/ajrccm.153.6.8665056
|View full text |Cite
|
Sign up to set email alerts
|

Serum indicators of free radical activity in idiopathic pulmonary fibrosis.

Abstract: Serum levels of free radical activity were measured in 37 patients with idiopathic pulmonary fibrosis (IPF) and 16 control subjects. Three assays used were (1) simultaneously measured levels of the 9,11-diene conjugate of linoleic acid and 9,12-linoleic acid expressed as a percent molar ratio (%MR), a measure of free-radical-mediated lipid peroxidation; (2) thiobarbituric acid reactive substances (TBARS), one of which is malondialdehyde; (3) desferrioxamine-chelatable iron assay, a measure of the potential iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Its antioxidant properties have also made it an attractive option for the treatment of patients with IPF, since the disease process has been associated with excessive oxidative stress (16),(17). NAC augments the synthesis of glutathione in vivo (18), replenishing stores and restoring the epithelial cell antioxidant defense mechanism.…”
Section: N-acetylcysteinementioning
confidence: 99%
“…Its antioxidant properties have also made it an attractive option for the treatment of patients with IPF, since the disease process has been associated with excessive oxidative stress (16),(17). NAC augments the synthesis of glutathione in vivo (18), replenishing stores and restoring the epithelial cell antioxidant defense mechanism.…”
Section: N-acetylcysteinementioning
confidence: 99%
“…Indeed, the oxidant burden in the lungs of patients with pulmonary fibrosis was found to be increased [65][66] and increased levels of H 2 O 2 and 8-isoprostane were found in the exhaled breath condensate of IPF patients [67]. Furthermore, in animal models for pulmonary fibrosis defective anti-oxidant mechanisms resulted in augmented fibrosis [16].…”
Section: Oxidative Stress Biomarkersmentioning
confidence: 99%
“…They also showed that increased peroxidase activity was involved in the epithelial injury in IPF [7]. Jackson et al reported that free radical activity was increased based on the change in serum markers [8], while Rahman et al showed an imbalance between oxidative stress and anti-oxidative potency in serum and BALF in IPF patients [9].…”
Section: Introductionmentioning
confidence: 99%